The Association between NOS3 Gene Polymorphisms and Hypoxic-Ischemic Encephalopathy Susceptibility and Symptoms in Chinese Han Population. - Wu, Yongqin; Zhu, Zhiling; Fang, Xiaoxia; Yin, Ling; Liu, Yuxia; Xu, Shouxia; Li, Aixue (BioMed Research International, 2016)
Endothelial NOS (NOS3) has a potential role in the prevention of neuronal injury in hypoxic-ischemic encephalopathy (HIE). Thus, we aimed to explore the association between NOS3 gene polymorphisms and HIE susceptibility and symptoms in a Chinese Han population. Three single nucleotide polymorphisms (SNPs) in the NOS3 gene, rs1800783, rs1800779, and rs2070744, were detected in 226 children with HIE and 212 healthy children in a Chinese Han population. Apgar scores and magnetic resonance image scans were used to estimate the symptoms and brain damage. The association analyses were conducted by using SNPStats and SPSS 18.0 software. The genotype and allele distributions of rs1800779 and rs1799983 displayed no significant differences between the patients and the controls, while the rs2070744 allele distribution was significantly different (corrected P=0.009). For clinical characteristics, the rs2070744 genotype distribution was significantly different in patients with different Apgar scores (≤5, TT/TC/CC = 6/7/5; 6~7, TT/TC/CC = 17/0/0; 8~9, TT/TC/CC = 6/2/0; 10, TT/TC/CC = 7/1/0; corrected P=0.006) in the 1001 to 1449 g birth weight subgroup. The haplotype test did not show any associations with the risk and clinical characteristics of HIE. The results suggest that NOS3 gene SNP rs2070744 was significantly associated with HIE susceptibility and symptom expression in Chinese Han population.